Mewujudkan Pembelajaran Transformatif melalui Taksonomi Fink dalam PSAP Fisika: Perspektif Pendidikan Kristen - Kurniawati Martha; Yanti Yanti (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
Learning should be understood as a process of seeking meaning that is coherent with students’ lives. However, current teaching practices still tend to focus on mere memorizing and the transfer of knowledge, leading to reductionism and a weakening of students’ internal development. This study aims to describe the implementation of transformative learning through Fink’s Taxonomy of Significant Learning in the course on Planning, Strategy, Assessment, and Physics Learning (PSAP Physics). The method used is a qualitative descriptive approach based on a literature review and implementation with 9 students. The results indicate that learning designed with consideration of situational factors, learning goals, teaching-learning activities, as well as feedback and assessment can develop all six dimensions of Fink’s framework: foundational knowledge, application, integration, the human dimension, caring, and learning how to learn. These findings suggest that a holistic approach fosters changes in students’ ways of thinking, their relationship with God, and their social responsibility. This study implies the importance of transformative learning design in creating meaningful learning experiences.AbstrakPembelajaran seharusnya menjadi proses pencarian makna yang koheren dengan kehidupan peserta didik. Namun, praktik pembelajaran masih cenderung berfokus pada hafalan dan transfer informasi, sehingga memunculkan reduksionisme dan melemahnya perkembangan internal peserta didik. Penelitian ini bertujuan mendeskripsikan implementasi pembelajaran transformatif melalui Taksonomi Pembelajaran Signifikan Fink dalam mata kuliah Perencanaan, Strategi, Assesment, Pembelajaran Fisika (PSAP Fisika).  Metode yang digunakan adalah deskriptif kualitatif berbasis studi literatur dan implementasi pada 9 mahasiswa. Hasil menunjukkan bahwa pembelajaran yang dirancang dengan memperhatikan situational factors, learning goals, teaching-learning activities, serta feedback and assessment mampu mengembangkan keenam dimensi Fink: foundational knowledge, application, integration, human dimension, caring, dan learning how to learn. Temuan ini menunjukkan bahwa pendekatan holistik mendorong perubahan cara berpikir, relasi dengan Tuhan, serta tanggung jawab sosial mahasiswa. Penelitian ini mengimplikasikan pentingnya desain pembelajaran yang transformatif untuk menghasilkan pengalaman belajar yang bermakna.